Understanding the Culture of Collaborative Attempts Among Academicians in Malaysia - Mansor, Mahani; Osman, Nazira; Nayan, Surina; Shafie, Latisha Asmaak; Maesin, Anis (International Journal of Advanced Corporate Learning (iJAC), 2010)
This paper attempts to understand the culture of collaborative attempts language academicians who are members of communities of practice share common professional activities. Participants of these communities of practice engage in a variety forms of collaborative attempts which include knowledge sharing via traditional means; conducting research, team teaching, mentoring, writing books and publishing articles, or online collaborative means; email, instant messaging, blogs, facebook, discussion groups and blogs. The paper discusses the trends of collaborative practices and the reasons for such collaborations.